2017
DOI: 10.1097/sih.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Feasibility and Predictive Validity of the SAGAT Tool to Assess Situation Awareness Among Medical Trainees

Abstract: The SAGAT is a valid, reliable tool for assessing surgical trainee SA. Information provided by the SAGAT can help diagnose team performance problems, inform debriefing discussion points, and inform curriculum development endeavors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…SAGAT is one method to directly measure SA and has been used in simulations with medical students,9 in trauma10 11 and in obstetric emergencies 12. One concern with SAGAT is potential intrusiveness, as simulation pauses are required 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SAGAT is one method to directly measure SA and has been used in simulations with medical students,9 in trauma10 11 and in obstetric emergencies 12. One concern with SAGAT is potential intrusiveness, as simulation pauses are required 7.…”
Section: Discussionmentioning
confidence: 99%
“…In general, to use SAGAT, simulations are paused multiple times. At each pause, participants are asked a group of questions to assess SA at three levels 7–12. Level 1 SA is the perception of the elements in the environment (eg, patient’s HR or SpO 2 , actions of other team members or equipment function).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original recommendation by Endsley was 30–60 items for within-subject studies for each of the three SA levels: (1) perception and attention, (2) comprehension and (3) projection 20. When Gardner et al validated a questionnaire based on SAGAT in a study of medical trainees, each questionnaire comprised three items for each level of SA at each freeze,25 while Hogan et al developed a questionnaire with three items at level 1, one item at level 2 and three items at level 3 22…”
Section: Methodsmentioning
confidence: 99%
“…One feature of SAGAT is that its use requires the simulation to pause,21 which might influence clinical understanding, both by impeding the suspension of disbelief in the simulation setting23 and by facilitating reflection on action 24. Gardner et al showed that it was feasible to use SAGAT to measure SA in the team training of surgical trainees in advanced cardiac life support 25. Globally, SAGAT has been used to study, for example, the effect of sleep deprivation on SA in trauma team training, how SA is associated with surgical trainee team performance, as well as nurses’ clinical assessment of patient deterioration 26–28.…”
Section: Introductionmentioning
confidence: 99%